Problems of complex rehabilitation of children with congenital cleft lip and palate during the COVID-19 pandemic and the introduction of martial law, their impact on the formation of dentognathic deformations - Filonenko Валерій Володимирович; Kaniura Олександр Андрійович; Bidenko Наталія Василівна; Yefymenko Владислав Петрович; Shpak Діна Юріївна (Actual Dentistry, 2023)
Introduction. The COVID-19 pandemic and the introduction of martial law significantly affected the provision of medical care to the population of Ukraine. The aim: analysis of the impact of the COVID-19 pandemic and the introduction of martial law on the formation of persistent dentognathic deformations in children with congenital cleft lip and palate. Materials and methods. A comparative analysis of the number of visits to dentists specializing in children’s treatment was carried out in the period from January 2018 to May 2023, the possibility of treatment according to the relevant protocols, the presence of complicationsand violations of the treatment plan forchildren with congenital cleft lip and palatewas evaluated. Results and their discussion. The problems of providing dental care, which affected the attendance of clinics, were analyzed. In order to comprehensively rehabilitate children with congenital cleft lip and palate, to prevent the formation of persistent forms of dentognathic deformations, the ways of their solution are outlined. Conclusions. In order to prevent the formation of persistent forms of dentognathic deformations and to achieve optimal results of complex rehabilitation, the most effective is the creation of a single register of children with congenital defects, a unified clinical protocol for orthodontic treatment, the introduction and development of the dental field of telemedicine, increasing the significance of the work of psychologists.